Enhanced efficiency and stability photovoltaic systems integrating improved MPPT photovoltaic systems / Mohd Hazni Abdul Halim Shah - Abdul Halim Shah, Mohd Hazni (2025)
This project conducts a comprehensive investigation into enhancing the performance of photovoltaic (PV) systems by integrating a Cuk converter with a Perturb and Observe (P&O) algorithm for Maximum Power Point Tracking (MPPT) under dynamic environmental conditions. The primary objective was to design and evaluate an MPPT system that combines a Cuk converter with the P&O algorithm to optimize energy extraction at varying irradiance levels. A methodical approach was employed, including an extensive literature review, system design, actual and simulated data simulations, and performance analysis. The system's response was evaluated under irradiance levels of 400 W/m2, 600 W/m2, and 1000 W/m2 to assess its accuracy, efficiency, and adaptability. The MPPT system consistently demonstrated accurate Maximum Power Point (MPP) tracking, achieving accuracy levels ranging from 98.32% to 98.35% across varying irradiance conditions. The system effectively transformed input power into usable output power with efficiency levels between 95.58% and 97.11%. The duty cycle profiles reflected the converter's adaptable operational behavior, maintaining a stable and predictable response to changes in irradiance. The results also revealed a strong correlation between increasing irradiance levels and proportional increases in input and output power, with the system achieving its highest performance at peak irradiance. These findings underscore the system's reliability, flexibility, and potential for practical applications in optimizing solar energy generation, making it a robust solution for renewable energy systems in diverse environmental settings.